'Crying Out With Life and Truth': Simulating Immersion in Messiaen's Des Canyons aux étoiles. . . Issue 2 (25th July 2017) - COCHRAN, TIMOTHY B.
Abstract: In Des Canyons aux étoiles. . ., a work commissioned to celebrate the American bicentennial, Olivier Messiaen defines the United States through representations of Utah's birds and canyons. Focusing on the phenomenological power rather than the pictorial intentions of Messiaen's music, this article examines ways that Messiaen uses textural saturation and varied repetition to draw the listener into a musically mediated Bryce Canyon. The music challenges a stable subject/object relationship for the listener by promoting humility and awe within the landscape over more visually oriented touristic encounters. Simulations of immersion serve implicit political and evangelistic goals as city-dwelling listeners are invited to embrace dwelling in the natural environment as a means of revaluing faith and breaking free from what Messiaen perceived as the twin hindrances of mechanized civilization and secularism.